The Nigerian child rights act 2003: its strengths and weaknesses (2014)
The enactment of the Child’s Rights Act 2003 (CRA) is an indication of Nigeria’s attempt to fulfil its obligation under the UN Child’s Rights Act (CRC)‘ and the African Charter on the Rights and Welfare of the Child (ACRWC)1 by domesticating these two treaties which specifically protect the rights of children.1 The paper aims to show the extent of the country’s conformity to its obligations under the CRC and the ACRWC. It critically analyses the CRA whether it conforms to the standards contained in these child rights treaties by examining the core provisions in the CRA. It is revealed that some aspects in the Act need to be reviewed to bring it into full compliance with international child rights law standards.On balance, the CRA guarantees and protects in numerous ways the rights of children in Nigeria